The Effect of Company Size on Accounting Conservatism in Manufacturing Companies Listed on the Indonesia Stock Exchange - Banggu, Hafrida; Dunakhir, Samirah; Hamzah, Hajrah (Universitas Negeri Makassar, 2023)
This study aims to determine whether the effect of company size on accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study is pharmaceutical companies listed on the Indonesia Stock Exchange, while the sample in this study consists of 11 companies listed on the Indonesia Stock Exchange and published complete financial statements during the 2019-2021 period. The results of this data analysis study show that a simple linear regression test shows that a constant value of 10,193 means that if the size of the company is zero, then accounting conservatism in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2021 is 10,193. The regression coefficient value of 0.937 means that if the company size variable increases by 1%, accounting conservatism in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange increases by 0.937. The results of the t-test obtained a sig value of 0.000 < 0.05, so it can be concluded that the size of the company has a significant effect on accounting conservatism in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The results of coefficient determination get a value of 0.387 / 38.7 percent, this means that the size of the company has a contribution or influence on accounting conservatism in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021 by 38.7 percent.